2017
DOI: 10.1007/s12350-016-0506-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a regimented aminophylline administration protocol on the burden of regadenoson-induced ischemia detected by SPECT myocardial perfusion imaging

Abstract: In patients undergoing regadenoson-stress SPECT-MPI, the intravenous administration of 75 mg of aminophylline as early as 90 seconds after radioisotope injection does not seem to attenuate the burden of myocardial ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…(2426) Administering aminophylline to prevent or treat regadenoson-related adverse effects has been shown to have no demonstrable effect on the burden of regadenoson-induced myocardial ischemia detected by SPECT-MPI. (27) Therefore, regadenoson is safe and generally well-tolerated in ESRD patients, and in January 2017, was approved by the Food and Drug Administration (FDA) for use in patients with ESRD. (28)…”
Section: Selection Of Stress Modality In Esrdmentioning
confidence: 99%
“…(2426) Administering aminophylline to prevent or treat regadenoson-related adverse effects has been shown to have no demonstrable effect on the burden of regadenoson-induced myocardial ischemia detected by SPECT-MPI. (27) Therefore, regadenoson is safe and generally well-tolerated in ESRD patients, and in January 2017, was approved by the Food and Drug Administration (FDA) for use in patients with ESRD. (28)…”
Section: Selection Of Stress Modality In Esrdmentioning
confidence: 99%
“…3,7 Aminophylline, a nonselective adenosine receptor antagonist, has been available on the market for decades and used to reverse the adverse effects of dipyridamole and adenosine and more recently been shown to be safe and effective for use with regadenoson. 8,9 In this issue of the Journal, Fughhi et al 10 address the concern that use of aminophylline to ameliorate the adverse effects of regadenoson may reverse its effects on coronary vasodilation and subsequent myocardial hyperemia reducing the sensitivity of MPI for detecting perfusion abnormalities. The data for the current study were pooled from two double-blinded, placebo-controlled randomized clinical trials, the ASSUAGE and ASSUAGE-CKD trials, 9,11 which demonstrated the effectiveness of aminophylline in attenuating the adverse effects associated with regadenoson in patients undergoing MPI.…”
mentioning
confidence: 99%
“…14 Thus, at least theoretically, antagonism of adenosine receptors at least 100 seconds after regadenoson administration should not interfere with myocardial uptake of the tracer. Based on these data, and allowing 10 seconds for the drug to reach the coronary capillary bed, The ASSUAGE trials, on which the study by Fughhi et al 10 is based, administered aminophylline at 90 seconds after tracer administration.…”
mentioning
confidence: 99%
See 2 more Smart Citations